2004
DOI: 10.1126/science.1103596
|View full text |Cite
|
Sign up to set email alerts
|

Femtomolar Sensitivity of a NO Sensor from Clostridium botulinum

Abstract: Nitric oxide (NO) is extremely toxic to Clostridium botulinum, but its molecular targets are unknown. Here, we identify a heme protein sensor (SONO) that displays femtomolar affinity for NO. The crystal structure of the SONO heme domain reveals a previously undescribed fold and a strategically placed tyrosine residue that modulates heme-nitrosyl coordination. Furthermore, the domain architecture of a SONO ortholog cloned from Chlamydomonas reinhardtii indicates that NO signaling through cyclic guanosine monoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
239
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(254 citation statements)
references
References 27 publications
11
239
1
3
Order By: Relevance
“…In the structure calculation process the heme is not constrained to be flat, hence the protein NMR restraints influence the conformation of the bound heme cofactor, particularly if they are within van der Waals contact of the heme ring. In analogy to a RDC-based structure ensemble of ubiquitin (38), we found that the width of the ranges of heme distortions observed in the Fe(II)-CO WT and Fe(II)-CO H103G structure ensembles are similar to the width of the ranges of heme distortions observed in X-ray crystal structures of other H-NOX domains (11,18,19,26). Thus, the differences observed between the two S. oneidensis NMR structure ensembles [Fe(II)-CO WT versus Fe(II)-CO H103G] reflect the conformational differences in the H-NOX protein scaffold induced by changes of the heme cofactor.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In the structure calculation process the heme is not constrained to be flat, hence the protein NMR restraints influence the conformation of the bound heme cofactor, particularly if they are within van der Waals contact of the heme ring. In analogy to a RDC-based structure ensemble of ubiquitin (38), we found that the width of the ranges of heme distortions observed in the Fe(II)-CO WT and Fe(II)-CO H103G structure ensembles are similar to the width of the ranges of heme distortions observed in X-ray crystal structures of other H-NOX domains (11,18,19,26). Thus, the differences observed between the two S. oneidensis NMR structure ensembles [Fe(II)-CO WT versus Fe(II)-CO H103G] reflect the conformational differences in the H-NOX protein scaffold induced by changes of the heme cofactor.…”
Section: Discussionmentioning
confidence: 67%
“…Average rms differences from the mean for this group of 20 lowest-energy structures were 0.33 Å for backbone and 0.94 Å for heavy atoms for Fe(II)-CO WT and 0.37 and 0.99 Å for Fe(II)-CO H103G. The overall topology of the H-NOX domain, with seven ␣-helices and four ␤-strands previously observed in X-ray studies of the H-NOX domains from T. tengcongensis (Tt) and Nostoc sp PCC 7120 (Ns), is preserved in the SO2144 H-NOX domain structure (11,18,19).…”
Section: Nmrmentioning
confidence: 89%
See 1 more Smart Citation
“…5,11,12 The H-NOX domain from Thermoanaerobacter tengcongensis (Tt H-NOX), which belongs to the second class of H-NOX domains, binds both NO and O 2 . A distal hydrogen-bonding network identified in the structure has been found to play a central role in O 2 binding.…”
Section: Introductionmentioning
confidence: 99%
“…sGC enzyme comprises an heterodimer α1β1 and a single Fe 2+ -haem moiety with the haem-binding site located to the β-subunit, where histidine residue 105 forms a covalent link to the Fe 2+ -centre of the haem group [208][209][210]. Structures of several bacterial orthologs of sGC which now are solved reveal molecular basis of sGC/NO interaction [211,212]. NO forms a five-coordinated NO complex with haem cofactor of β-sGC subunit which leads to a hundred-fold more active conformation of the heterodimer, e.g.…”
Section: No Targetsmentioning
confidence: 99%